Identification of genetic variants in two families with Keratoconus - Qinghong Lin; Xuejun Wang; Tian Han; Xingtao Zhou (BMC, 2023)
Abstract Background This research investigated the genetic characteristic of two Chinese families with keratoconus (KC). Methods For all people in the two families with KC, their history, clinical data, and peripheral blood were collected. One hundred healthy participants without KC and 112 sporadic KC patients were recruited as the controls. Whole exome sequencing of the genomic DNA and polymerase chain reaction were conducted for all the controls and family members to verify the variants. Functional analyses of the variants was performed using the software programs. Results A missense tuberous sclerosis 1 (TSC1) variant g.135797247A > G (c.622A > G, p.Ser208Gly) was detected in family 1. A single nucleotide polymorphism (SNP) rs761232139 (p.Gly235Arg) in aldehyde dehydrogenase 3 family member A1 (ALDH3A1) gene was detected in family 2. The variant c.622A > G in TSC1 and the SNP rs761232139 in ALDH3A1 were predicted as being probably damaging. Conclusions Novel variant c.622A > G in TSC1 and SNP rs761232139 in ALDH3A1 have been detected in families with KC. These two findings may play a role in the pathogenesis of KC.